ĐÁNH GIÁ CƠ QUAN ĐIỆN TỬ THEO MÔ HÌNH ITI – GAF - Nguyễn Ái Việt, Đoàn Hữu Hậu, Ngô Doãn Lập, Đỗ Thị Thanh Thùy, Lê Quang Minh (ĐHQGHN, 2016)
ITI-GAF model was developed from experiences in building EA in the world and simplified to suit Vietnam’s context. Besides, ITI-GAF model can be used as a methodology for making an exact and effective current status assessment of IT applying in Vietnam’s agencies. We also suggested a new concept named e - organization which is considered as a mid - milestone for building e-government. Based on this approach, we made an assessment of the IT applying maturity in one government agency and created some lessons learned to apply broadly in VietNam.